THE EFFECT OF DUTY ON THE ACQUISITION OF LAND AND BUILDING RIGHTS TO THE ORIGINAL INCOME OF THE REGION - Sri Wahyuni Nur (Salewangang Institut Publishing, 2018)
This study aims to determine of the influence of Duty on the Acquisition Rights of Land and Building on Original Income of Region of Maros. The method of analysis in this study is a simple regression analysis, correlation, determination and hypothesis testing. The test result states that the hypothesis is accepted that Probability is less than the significant level (0.003 <0.05) means that of Duty on the Acquisition Rights of Land and Building has significant effect on Original Income of Region of Maros. Result of the research showing that the suggestion is given to do the program of socialization of local regulation, one of Maros Regency Regulation concerning the duty of acquisition of land and building rights to the Taxpayer.